2021
DOI: 10.3390/cancers13102319
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adjuvant Therapy Decision: Results of a Real-World Multicenter Data Analysis of 904 Melanoma Patients

Abstract: Adjuvant treatment of melanoma patients with immune-checkpoint inhibition (ICI) and targeted therapy (TT) significantly improved recurrence-free survival. This study investigates the real-world situation of 904 patients from 13 German skin cancer centers with an indication for adjuvant treatment since the approval of adjuvant ICI and TT. From adjusted log-binomial regression models, we estimated relative risks for associations between various influence factors and treatment decisions (adjuvant therapy yes/no, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 60 publications
1
20
1
1
Order By: Relevance
“…In our center, the tumor board recommended adjuvant treatment for the vast majority of the patients with stage III/IV NED melanoma, with only very few patients (4.6%) deemed ineligible due to severe comorbidities. The acceptance rate of adjuvant treatment by our patients was 90.8% and higher than in a German cohort reported by Lodde et al where 76.9% opted for an adjuvant treatment [10]. More patients were prescribed pembrolizumab (52.9%) than nivolumab (42.9%).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In our center, the tumor board recommended adjuvant treatment for the vast majority of the patients with stage III/IV NED melanoma, with only very few patients (4.6%) deemed ineligible due to severe comorbidities. The acceptance rate of adjuvant treatment by our patients was 90.8% and higher than in a German cohort reported by Lodde et al where 76.9% opted for an adjuvant treatment [10]. More patients were prescribed pembrolizumab (52.9%) than nivolumab (42.9%).…”
Section: Discussioncontrasting
confidence: 62%
“…Lodde et al recently reported that BRAF V600E/K patients treated in German centers preferred ICI (52.9%) over BRAFi/MEKi (47.1%) and that this choice was strongly influenced by physicians' preferences [10]. This striking difference in prescription rate of BRAFi/MEKi between our center and the German centers suggests significant regional disparities in clinical practice possibly influenced by physicians' preferences, local guidelines, and patient's perceptions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Treatment decisions are based on several (individual) variables and preferences of patients and physicians alike, including a risk assessment of the induction of potentially life‐changing AEs all of which might have influenced the results of this work 19 . It is also worth noticing that this study only included patients from skin cancer centers in the DACH‐region.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment decisions are based on several (individual) variables and preferences of patients and physicians alike, including a risk assessment of the induction of potentially life-changing AEs all of which might have influenced the results of this work. 19 It is also worth noticing that this study only included patients from skin cancer centers in the DACH-region. Limitations of this study further include its retrospective design and that a small number of patients was still receiving adjuvant treatment at the time of data cut-off (October 2021).…”
Section: Discussionmentioning
confidence: 99%